2011
DOI: 10.1161/circep.111.965830
|View full text |Cite
|
Sign up to set email alerts
|

Low-Energy Multistage Atrial Defibrillation Therapy Terminates Atrial Fibrillation With Less Energy Than a Single Shock

Abstract: Background-Implantable device therapy of atrial fibrillation (AF) is limited by pain from high-energy shocks. We developed a low-energy multistage defibrillation therapy and tested it in a canine model of AF.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
34
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 47 publications
(36 citation statements)
references
References 53 publications
2
34
0
Order By: Relevance
“…In 2009, F. Fenton, S. Luther et al demonstrated in-vitro that atrial fibrillation can be terminated using a series of low-energy shocks instead of one high-energy shock [135], achieving an energy reduction of more than 85%. Similar energy reduction was observed by W. Li et al and C. M. Ambrosi et al using a multi-stage atrial defibrillation technique [136,137]. For the study by Fenton and Luther, the effectiveness of the method was attributed to the recruitment of many wave sources throughout the tissue and the progressive activation of more and more volume with subsequent waves emitted from these sources (with a stimulation period on the time scale of the arrhythmia).…”
Section: This Thesissupporting
confidence: 64%
“…In 2009, F. Fenton, S. Luther et al demonstrated in-vitro that atrial fibrillation can be terminated using a series of low-energy shocks instead of one high-energy shock [135], achieving an energy reduction of more than 85%. Similar energy reduction was observed by W. Li et al and C. M. Ambrosi et al using a multi-stage atrial defibrillation technique [136,137]. For the study by Fenton and Luther, the effectiveness of the method was attributed to the recruitment of many wave sources throughout the tissue and the progressive activation of more and more volume with subsequent waves emitted from these sources (with a stimulation period on the time scale of the arrhythmia).…”
Section: This Thesissupporting
confidence: 64%
“…This method is called low-energy antifibrillation pacing (LEAP). With much faster pacing rates than the cycle length, similar energy reductions were found for AF 15,16 , while for VT the energy may further be reduced by an order of magnitude 14,17 .…”
Section: Introductionmentioning
confidence: 52%
“…Multistage electrotherapy using multistage biphasic shocks delivered between the left and right atrial vectors significantly reduce atrial defibrillation threshold to <1 J (0.19-0.51 J) in a canine model of induced AF. 41 Multistage electrotherapy using monophasic shocks delivered between transvenous RV and coronary sinus coils within a single VT cycle length significantly reduced the mean ventricular defibrillation threshold for antitachycardia pacing-refractory monomorphic VTs to nearly 80-fold lower energy that a biphasic shock (0.03±0.05 versus 2.37±1.20 J; P<0.001). 42 Moreover, at a peak shock amplitude of 20 V, multistage electrotherapy was significantly more effective than biphasic shock in terminating VT (91.3% versus 10.5%;…”
Section: Low-energy Multistage Electrotherapy For Atrial and Ventricumentioning
confidence: 93%